Feminism in film theory. The status of the issue - Molina García, Berta (Comunicación y Género [Communication and Gender], 2021)
This paper focuses on the review of main bibliographic sources of feminist film history from the 1960s to the 21th Century. It addresses fundamental aspects like women’s representation in cinema and other mass media, women’s place in narrative and how the arrival of technology has been a tipping point to understand new proposals from a feminism that advocates for opening new paths and suggests new realities outside the masculine / feminine binary. We will see how, throughout the years, feminism has changed its focus of study.
Keywords: feminist film history; gender studies; cinematographic representation